Analisis Kenyamanan Thermal Pada Ruang Pendaftaran Pasien Gedung RSUD Meuraxa Banda Aceh - Junaidi Junaidi; Ahmad Syuhada; Zahrul Fuadi (Jurnal Teknik Mesin Unsyiah, 2015)
The improvement status of RSUD Meuraxa from non referral to full service and equipped hospital brought several implications to the hospital services particularly in dealing with the increase of patients. The increasing flow of patients in line results in the escalation of the room temperature. The condition was affected by thermal inconveniency caused by direct thermal radiation from the sun, embedded and congenital metabolism of patients (Met), patient clothing insulation (Clo), room equipments and room air circulation. The phenomena affect human performance in their activities. To maintain its status as a general hospital, the impaired condition should be addressed by knowing first the source of the cause. Several measures are normally conducted through direct assessment of the room thermal condition involving the temperature measurement, relative humidity, rate of air flow, and sun ray intensity. Based on the measurement and analysis, it is found that the increase in the room’s occupation has resulted in average increase of room temperature and relative humidity of 30C and 2%, respectively.Themaximum indoor temperature reached 360 while the minimum humidity was 44%. The average indoor air flow rate was less than 1 m/s. It is suggested that one possible solution to improve the thermal inconvenience on the room is by installing the air blower to improve the air circulation of the room.